Pengaruh Word Of Mouth, Kesadaran Merek dan Kualitas Produk terhadap Keputusan Pembelian (Studi Pada Mie Akhirat di Surabaya) - Linggar Apriliya (BISMA (Bisnis dan Manajemen), 2018)
The development of food bussiness in Indonesia which growing rapidly make the competition even more intense. As one of the bussiness of food Mie Akhirat must have competitive superiority in order to survive to win the competition in culinary bussiness. This study used 188 samples, the sampling method is nonprobability sampling with purposive sampling technique. While measuring instrument used was a questionner, the data were analyzed using multiple regression analysis with SPSS for Windows 16. The results of this study showed that brand awareness and product quality has significant impact on purchase decision. While word of mouth has no significant impact on purchase decision.